BAHASA ARAB SEBAGAI DISTINGSI UNGGULAN DAN SELING POWER RAUDLATUL ATHFAL - Eman Sulaeman (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2020)
This paper examines the quality of human resources and the welfare of RA teachers, which so far still show a number of limitations. These two problems need to be studied, along with the large gap between the basic education levels (early education / preschool) and secondary and tertiary education. Whereas PAUD education is the basic development for junior and senior high education. The purpose of this study was to capture the quality of human resources and the welfare of RA teachers, as well as the alternatives offered to solve these two problems. Based on the results of field studies, it can be described that the quality of RA teachers (especially in the city of Bandung) is generally still low. This can be seen from the input qualifications of RA teachers who on average graduate from high school or undergraduate non-PAUD education. Likewise, the teacher competency input still does not meet the standards. Meanwhile, in the aspect of welfare, the average monthly honorarium for RA teachers is around Rp. 300 000, -. This nominal is much lower than the UMR in Bandung, which is currently around Rp. 2.3 million rupiah. Responding to this low quality and welfare, the researcher offers the concept of strengthening the quality of Arabic for RA teachers as a first step in creating distinctions (uniqueness) in the school. Based on the field analysis, schools that have a distinction in language (Bilingual Kindergarden-for example) generally have high selling power so that the problem of low recognition and teacher welfare can be resolved. ABSTRAK Paper ini mengkaji tentang mutu SDM dan kesejahteraan guru RA yang selama ini masih menunjukan sejumlah keterbatasan. Dua persoalan tersebut perlu dikaji, seiring dengan adanya kesenjangan yang begitu jauh antara jenjang pendidikan dasar (pendidikan usai dini/prasekolah) dengan pendidikan ditingkat menengah dan tinggi. Padahal pendidikan PAUD merupakan basic pengembangan untuk jenajang pendidikan menengah dan atas. Tujuan penelitian ini yaitu untuk memotret mutu SDM dan kesejahteraan guru RA, serta alternative yang ditawarkan untuk pemecahan kedua persoalan tersebut. Berdsarkan hasil studi lapangan, dapat digambarkan mutu guru RA (khususnya di kota Bandung) umumnya masih rendah. Hal ini bisa dilihat dari input kualifikasi guru RA yang rata-rata tamatan SMA atau S1 non pendidikan PAUD. Demikian juga dari input kompetensi guru masih belum memenuhi standar. Sedangkan dalam aspek kesejahteraan, honorarium bulanan guru RA rata-rata berada di kisaran Rp. 300 000,-. Nominal ini jauh lebih rendah dibanding UMR kota Bandung yang saat ini berada di kisaran Rp. 2,3 juta rupiah. Menyikapi rendahnya mutu dan kesejahteraan ini, peneliti menawarkan konsep penguatan mutu bahasa Arab bagi guru RA sebagai langkah awal melahirkan distingsi (kekhasan) di sekolah tersebut. Berdsarkan analisis lapangan, sekolah-sekolah yang memiliki distingsi dalam kebahasaan (Bilingual Kindergarden-misalnya) umumnya memiliki daya jual (selling power) yang tinggi sehingga persoalan rendahnya pengakuan dan kesejahteraan guru dapat teratasi